Incidence of Typhoid Fever Infection among Febrile Patients attending FUDMA Clinic - Abduljalil, Nafisa Adamu; Abah , Oche Clement; Sagir, Hafsat Bakori (Sahel Journal of Life Sciences FUDMA, 2024)
Typhoid fever remains a public health concern in Nigeria, with its incidence poising substantial challenges to health care systems. Widal agglutination test is largely the only used diagnostic test method for the laboratory diagnosis of Typhoid infection which has been proven to be neither sensitive nor specific. This paper delves into the incidence, contributory factors as well as sensitivity and specificity of commonly used diagnostic tests of typhoid fever infection among febrile patients attending the FUDMA Clinic. A total of 55 Blood and stool samples were analyzed using standard procedures for slide agglutination test (Widal) and stool culture, before culturing, the samples were first inoculated in an enrichment medium (Selenite-F broth). After 4 hours of pre-enrichment, the samples were inoculated into Salmonella Shigella Agar and Mackonkey agar, while catalase, TSI, citrate utilization test, Indole test, and urease tests served to identify the organism biochemically. Socio-demographic data revealed that 55 Participants, 52.8% were males, 72.7% were students and 80% were singles. Slide agglutination test recorded a 90.9% incidence rate, stool culture had an incidence rate of 18.18%. Among the age groups that enrolled in this study, a 44.1% incidence rate was recorded among the age Group 20-26 years. Stool culture was to found have performed better diagnostically with a sensitivity of 60% as well as a specificity of 40%. Conclusively, A high Incidence of typhoid fever was observed in this study. This Therefore suggests that there is an urgent need for improved personal hygiene and more accessibility to potable drinking water.